KINERJA KEUANGAN BANK MILIK PEMERINTAH INDONESIA (Studi Kasus : BNI, BRI, BTN, Bank Mandiri) - Ahmad Soleh; Yun Fitriano (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to analyze the comparison of the financial performance of state-owned banks and provide empirical evidence of the effect of LDR, CAR, and NPL on ROA. This analysis uses an independent variable of liquidity and solvency. The independent variable is focused on CAR, LDR, NPL, while the dependent variable is profitability focused on ROA. The data used are secondary data derived from the annual financial statements of BNI, BRI, BTN, Bank Mandiri listed on the Indonesia Stock Exchange in the period 2008 to 2015. The method of testing data uses, classic assumption test, multiple linear regression, coefficient of determination (R2 ), by testing the hypothesis t test and F test. The results showed that the multiple linear regression equation Y = 1.145 + 0.023 X1 + 0.004 X2 - 0.281 X3. Partial test (t test) shows that the LDR ratio of government-owned banks has a positive and significant effect on ROA with a t count of 3.108 > t table 1.693 with a significant level of 0.0046 or 0.46%. CAR ratio has a positive effect and is not significant for ROA with a t count of 0.126 < t table 1.693 with a significant level of 0.9004 or 90.4%. The NPL ratio has a negative and not significant effect on ROA with a tcount of -4.594 < t table 1.693 with a significant level of 0.0001 or 0.01%. Simultaneous testing (F test) shows the ratio of LDR, CAR, and NPL has a positive and significant effect on ROA with a calculated F value of 26.414 > t table 2.93 with a significant level of 0.000 or 0.0%. The results of testing the coefficient of determination (R2) shows that the independent variables LDR, CAR, and NPL can explain the effect on the dependent variable ROA, which is equal to 0.863 or 86.3% while 13.7% is influenced by other variables not examined.